INTERNATIONAL EXPERIENCE OF STIMULATING ENTREPRENEURSHIP IN THE CONTEXT OF INVESTMENT POLICY - Врублевський, Іван; Танасієнко, Наталія (SWorldJournal, 2026)
The article examines the international experience of forming and implementing investment policy as a tool for stimulating entrepreneurship. The main approaches of foreign countries to supporting small and medium-sized enterprises using tax incentives, di